PeningkatanKewirausahaan danLife SkillMahasiswa Melalui Teknik Eksperimen PupukOrganik Kascing padaMataKuliah Evaluasidan Konservasi Sumber Daya LahanJurusan Pendidikan Geografi - Elfayetti Elfayetti; Herdi Herdi; Rosni Rosni; Kamarlin Pinem (Universitas Negeri Medan, 2014)
This research aims to realize the implementation increase enterpreunership and lifeskill of the students bykascing organic waste as experiment method experiment technic in subject Evaluation and Conservation ofFarm Resource Geography Education Department. This research is carried out July until November 2012 atGeography Education Department. Data that got to outcome of the research by student and the lecture.The activity of research devided for four cycle, consist of planning, action, experiment and reflection. Resultthat got to show that increase value of the students by the cycle. By using theProblem Based Instruction(PBI) model every student in group can identify and analysis the result from field research.